Multimodal analysis of in vivo resorbable CaP bone substitutes by combining histology, SEM, and microcomputed tomography data. Issue 4 (2nd August 2017) - Sweedy, Ahmed; Bohner, Marc; Baroud, Gamal
Abstract: This study introduced and demonstrated a new method to investigate the repair process of bone defects using micro‐ and macroporous beta‐tricalcium phosphate (β‐TCP) substitutes. Specifically, the new method combined and aligned histology, SEM, and preimplantation microcomputed tomography (mCT) data to accurately characterize tissue phases found in biopsies, and thus better understand the bone repair process. The results included (a) the exact fraction of ceramic remnants (CR); (b) the fraction of ceramic resorbed and substituted by bone (CSB); and (c) the fraction of ceramic resorbed and not substituted by bone (CNSB). The new method allowed in particular the detection and quantification of mineralized tissues within the 1–10 µm micropores of the ceramic ("micro‐bone"). The utility of the new method was demonstrated by applying it on biopsies of two β‐tricalcium phosphate bone substitute groups with two differing macropore sizes implanted in an ovine model for 6 weeks. The total bone deposition and ceramic resorption of the two substitute groups, having macropore sizes of 510 and 1220 μm, were 25.1 ± 8.1% and 67.5 ± 3.2%, and 24.4 ± 4.1% and 61.4 ± 6.5% for the group having the larger pore size. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 1567–1577, 2018.